KARAKTERISTIK PENDERITA TB PARU KATEGORI 2 RAWAT JALAN DI BALAI PENGOBATAN PENYAKIT PARU-PARU (BP4) LUBUK ALUNG SUMATERA BARAT TAHUN 2015-JUNI 2016 - Tryani Walnizam Junaidi; Sori Muda Sarumpaet; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
The category-2 pulmonary tuberculosis’s patients are patients who have to undergo re-treatment which has received treatment with anti-tuberculosis drugs before and has more risk of drugs resistance. Based on TB report in West Sumatera province, there’re 268 cases of TB in category-2. The amount of patients with pulmonary TB 2 categories based outpatient medical record in Lubuk BP4 Alung 2015-June 2016 are 146 cases. The purpose of this research is to analyze the characteristics of pulmonary tuberculosis patients in category 2, the research will be conducted in BP4 Lubuk Alung West Sumatra in case series design . The amount of population in this research are 146 people in 2015 to June 2016 in the medical record and the sample of this research is total sampling. Univariate data were analyzed by descriptively and bivariate data were analyzed by using Chi-square, Fisher Exact, and Kolgomorov-Smirnov. Based on the sociodemographic, the highest proportion is in the age group of namely 55-64 years (23,3%), males (63,0%), farmers/ fisherman/labors (28,1%), the West Sumatra province (92,5%). The highest proportion is based on the results of BTA test (87,0%), the type of patients relapsed (69,2%), history of diabetes mellitus (17.8%), smoking (58,2%), no alcohol consumption (94,5% ), a complication of spontaneous pneumothorax (13,7%). There was no significant difference in the proportion of age based on the type of patients (p=0,227), gender based on the types of patients (p=0,901), the results of the examination with the type of patient (p=0,999), disease history is based on the type of patients (p=0,547), smoking and type of patients (p=0,835), alcohol habits with the type of patients (p=0,418), based on the type of patient complications (p=0,806). This is suggested BP4 to give more intensive information to category-2 patient to obey the medication rule completely to avoid relapse and failure of treatment convertion and more risk of getting TB-MDR. They also have to keep their immune system by maintain a healthy lifestyle. Keywords: Pulmonary tuberculosis in category-2, the characteristics of the patients, outpatient